FORMATION OF THE INTERCULTURAL COMPETENCE OF STUDENTS-ECONOMISTS IN TEACHING BUSINESS COMMUNICATION - Семенчук, Юлиан (Verbum, 2015)
The problem of forming and improving intercultural competence of students is being studied in the general context of teaching foreign languages and is in the focus of the researchers’ attention, as the expanding of business contacts and the globalization of economic life put forward such a task. Therefore, the students of economic specialities, who specialize in the sphere of international economic relations, need not only to develop the skills of business communication in a foreign language, but also in the study of cross-cultural business communication features. The process of mastering basics of oral and written business communication in a foreign language by the students must be organized in interactive forms of work with sample documents, authentic texts for reading and listening to learn the terminology, expand the knowledge of socio-cultural context of business contacts and learn how to apply this knowledge in modeling situations of business communication. The use of interactive teaching methods in the classroom and individual work will allow students to solve business problems, develop their creative abilities in the process of professionally oriented activities and learn cross-cultural communication standards. Review of the theoretical assumptions for the formation and improvement of students’ intercultural competence as a structural component of professional foreign language communicative competence, justification for the use of interactive forms of work, study of their teaching capacities and development of effective exercises is the result of this article. The use of sound theoretical and practical conclusions offered in this paper would contribute to enhancing the effectiveness of joint training of teachers and students in accordance with modern requirements for foreign language education at universities and the needs of the trainees.
Keywords: intercultural competence; interactive forms of work; business communication; foreign language